2014
DOI: 10.5056/jnm.20.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Pharmacologic Therapies for Constipation-predominant Irritable Bowel Syndrome and Chronic Constipation

Abstract: Irritable bowel syndrome with constipation and chronic functional constipation are common digestive disorders that negatively impact quality of life and account for billions of dollars in health care costs. Related to the heterogeneity of pathogenesis that underlie these disorders and the failure of symptoms to reliably predict underlying pathophysiology, traditional therapies provide relief to only a subset of affected individuals. The evidence surrounding new and emerging pharmacologic treatments, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…[2][3][4][5] In the past, therapy has been symptom-based, but recent advances in the understanding of the pathophysiology have led to the development of therapies directed at specific phenotypes of IBS, such as serotonergic agents and prosecretory agents. 6,7 However, the treatments are still unsatisfactory in some patients. Recently, the involvement of microbial factors, such as alterations in the gut microbiota, has been suggested as a possible etiological mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4][5] In the past, therapy has been symptom-based, but recent advances in the understanding of the pathophysiology have led to the development of therapies directed at specific phenotypes of IBS, such as serotonergic agents and prosecretory agents. 6,7 However, the treatments are still unsatisfactory in some patients. Recently, the involvement of microbial factors, such as alterations in the gut microbiota, has been suggested as a possible etiological mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Studies have shown that serotonergic agents, acting primarily through 5-HT 3 and 5-HT 4 receptors, provide clinical benefit to patients with functional GI disorders including IBS. 6,25,27 The 5-HT 4 receptor agonist prucalopride accelerates colonic transit and has been effective in patients with chronic constipation. 28,29 Mosapride citrate (mosapride) is a selective 5-HT 4 receptor agonist, and its metabolite has a weak 5-HT 3 receptor antagonistic effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…87 Bile acids that are not absorbed in the terminal ileum can stimulate water and electrolyte secretion in the colon and directly contribute to colonic motility independent of secretory effects. 104 A subset of patients with IBS-C may exhibit lower bile acid levels in their stools than in those of healthy controls and of patients with diarrhoea-predominant IBS, 87 which may be attributed to altered bile acid synthesis in these patients. 105 Modulation of the bile acid cycle may help treat chronic constipation and involves bile acid supplementation or inhibition of the ileal bile acid transporter.…”
Section: Bile Acid Modulationmentioning
confidence: 99%